PERTIMBANGAN HAKIM DALAM PUTUSAN PEMIDANAAN PELAKU TINDAK PIDANA PERDAGANGAN ORANG - Hartono, Yohana Liely Klarita (JURNAL PANAH KEADILAN, 2024)
The crime of trafficking in persons is the act of recruiting, transporting, hiding, sending, transferring or receiving someone with the threat of violence, use of violence, kidnapping, confinement, forgery, fraud, abuse of power or position, one of which is the crime of trafficking in persons which is tried by a panel of court judges. . Kupang State, this research is entitled Judges' Considerations in Handing Down Decisions for Perpetrators of the Crime of Human Trafficking (Decision Study Number 178/Pid.Sus/2021/PN.Kpg). The type of research used is normative legal research using a statutory approach, case approach and analytical approach. Data collection was carried out using primary, secondary and tertiary data. The data analysis used is qualitative descriptive analysis and conclusions are drawn using deductive methods. Based on the results of the research and discussion, the researcher assesses that there was an error in the sentencing where the defendant should not only be sentenced to prison but accompanied by a fine of at least 120,000,000.00 million rupiah and a maximum of 600,000,000.00 million rupiah, namely in accordance with article 6 number 21 of 2007 concerning Eradication of the Crime of Human Trafficking. The panel of judges who examine and decide a criminal case of human trafficking must be more careful in giving punishment to individuals who commit criminal acts in accordance with applicable laws and regulations, so as to create justice, legal certainty and usefulness with the applicable regulations. .